Social Solidarity in the Jum’at Berkah Movement Foundation - Ocs Relly Yantika; Yulia Nora, Vivi (BELIEF: Sociology of Religion Journal, 2024)
Yayasan Gerakan Jum'at Berkah Berkah is a social organization that is committed to conducting social movements for the people of Duri city. Solidarity between foundation administrators is the most important factor in the effectiveness of the foundation. So the purpose of this research is to find out more deeply, namely how the Solidarity Mechanism of the Blessed Friday Movement Foundation in the city of Duri. The research methodology used in this research is qualitative descriptive research, namely data collection through interviews, observation, and documentation. Reducing data, presenting data, and drawing conclusions are steps in data analysis. Expanding observation, increasing persistence, and triangulation are methods to ensure data validity. Using the snowball sampling technique, informants were contacted. The results of this research on the Blessed Friday Movement Foundation form solidarity within the foundation's board members and have a positive impact on the city of Duri and surrounding communities. This movement is also supported by sponsors and regular donors in the city of Duri. The Blessed Friday Social Movement can be an effective effort to help the people of Duri city. The Blessed Friday Movement also forms strong solidarity, creates togetherness, cooperation, solidarity, and participation in board members, strengthens friendship and becomes a link between individuals with individuals, individuals with groups and groups with groups, and useful involvement and empowerment.